A study of two groups of navy in identifying type of emotions, regulating and understanding emotions - Getrude Cosmas; Raja Nor Hanif Raja Kamarulzaman (Fakulti Psikologi dan Pendidikan, 2021)
Emotion is one of the attitude elements which can affect they way people think and behave. People convey messages through verbal cues and through emotions which is display via facial expression. In regard to this, not all can identify the seven type of basic emotions and this sometimes brings about confusion and misunderstanding in communication. Therefore, it is important to enhance the level of accuracy in identifying others’ emotional expression which may help someone to regulate and understand others’ emotion well. The aims of the study is to examine the differences between the experimental and control groups of Navy in terms of identifying types of emotions, regulating and understanding other’s emotion (empathy). The participants were divided into two groups; the experimental group (n=25) took part in the emotion management workshop, while the control group (n=25) did not. All of them were selected randomly into the groups. A set of questionnaires consisting of four parts was used; Part A measured demographic profile, Part B measured emotional regulation, Part C measured empathy and Part D measured the identification of seven types of emotions. For the experimental group, the questionnaire was given after the one day emotion management workshop. The study found that the the experimental group could identify emotions more accurately compared to the control group as measured by seven pictures portraying different type of emotions. Regarding emotional regulation and understanding emotions (empathy), the two groups did not show any significant differences. This study showed that understanding and differentiating various types of emotions may help enhance participants’ level of accuracy in identifying types of emotions that are displayed through different facial expressions. For emotional regulation and empathy, although both are innate, a comprehensive workshop and training which allocates more time for participants to learn and apply relevant skills in real life experiences might ne needed.